2009
DOI: 10.1161/circheartfailure.109.885301
|View full text |Cite
|
Sign up to set email alerts
|

On the Control of Metabolic Remodeling in Mitochondria of the Failing Heart

Abstract: T he metabolic phenotype of the failing heart may be defined as follows. 1 Metabolism remodels in the failing heart, leading to a loss in energy reserve and the inability to increase ATP supply. Ultimately, this metabolic rigidity leads to a fall in ATP. The likely time line is decreased energy reserve via the phosphotransferase reactions (creatine kinase [CK] and adenylate kinase) leading to increases in ADP and AMP, triggering an increase in glycolysis. Although the contribution of glycolysis to overall ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…On the other hand, PCr and CK activity, central to high-energy phosphates in the cardiomyocyte and the transfer of energy from mitochondria to essential cytosolic ATPase, were significantly increased. This pattern is opposite to that which is observed in failing hearts [27, 28], indicating energy reserve in the repetitive coronary stenosis model can be utilized in situations of ischemic stress or increased contractile demand. Previous studies of the repetitive coronary stenosis model and short term hibernating myocardium have shown upregulation of glucose uptake, increases in anaerobic metabolism and optimization of energy utilization [3, 21, 22, 26, 29, 30].…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, PCr and CK activity, central to high-energy phosphates in the cardiomyocyte and the transfer of energy from mitochondria to essential cytosolic ATPase, were significantly increased. This pattern is opposite to that which is observed in failing hearts [27, 28], indicating energy reserve in the repetitive coronary stenosis model can be utilized in situations of ischemic stress or increased contractile demand. Previous studies of the repetitive coronary stenosis model and short term hibernating myocardium have shown upregulation of glucose uptake, increases in anaerobic metabolism and optimization of energy utilization [3, 21, 22, 26, 29, 30].…”
Section: Discussionmentioning
confidence: 66%
“…It is observed that in both the aging [3,4] and the diseased heart [8][9][10][11][12] relationships between cardiac work rate and concentrations of phosphate metabolites ATP, ADP, and phosphocreatine (CrP) are altered. In heart failure ATP and the CrP/ATP ratio is diminished and [ATP] in myocardium is lower compared to healthy individuals [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, subunit c of F o F 1 -ATP synthase has three isoforms (P1, P2, and P3), encoded by ATP5G1, ATPG2, and ATPG3 genes [12]. Recently, we showed that subunit c of F o F 1 -ATPase might be a structural and/or regulatory component of the mPTP complex, whose activity might be modulated by calcium-dependent phosphorylation [13].Alterations in mitochondrial bioenergetics play important roles in the origin and progression of myocardial ischemia [14], manifesting as inhibition of respiratory complex activity, increased proton leakage from the inner mitochondrial membrane [15], increased ROS production [16], mitochondrial calcium overload [17], and finally, opening of mPTP [18]. During the development of myocardial ischemia, oxygen deprivation alters mitochondrial function and ATP synthesis, causing an important reduction in cardiac ATP production [19].…”
mentioning
confidence: 99%
“…Alterations in mitochondrial bioenergetics play important roles in the origin and progression of myocardial ischemia [14], manifesting as inhibition of respiratory complex activity, increased proton leakage from the inner mitochondrial membrane [15], increased ROS production [16], mitochondrial calcium overload [17], and finally, opening of mPTP [18]. During the development of myocardial ischemia, oxygen deprivation alters mitochondrial function and ATP synthesis, causing an important reduction in cardiac ATP production [19].…”
mentioning
confidence: 99%